Starlikeness Of Certain Integral Operators And Properties Of A Subclass Of Close To Convex Functions - Chung, Yao Liang (2017)
The present dissertation investigates the sufficient conditions for an analytic function to be starlike in the open unit disk D and some properties of certain subclass of close-to-convex functions. A brief survey of the basic concepts and results from the classical theory of analytic univalent functions are given. Sufficient conditions for analytic functions satisfying certain third-order differential inequalities to be starlike in D is derived. As a consequence, conditions for starlikeness of functions defined by triple integral operators are obtained. Connections are also made to earlier known results.